Professional burnout of nurses employed in non-invasive treatment wards - Tomaszewska, Katarzyna; Majchrowicz, Bożena (Journal of Education, Health and Sport, 2019)
Nursing is a profession characterized by multidimensionality, multitasking and a high degree of difficulty. Its performance is associated with exposure to many stressors, which are associated with the provision of help, rescue and protection of human life. The biggest consequences of stress in the work of nurses include the burnout syndrome, which leads to treating the mentees as objects and abandoning the profession. The specificity of work and the involvement of nurses, caring for the good of the patient is a huge psychological burden, which in many cases may lead to the occurrence of so-called burnout syndrome.Purpose of the studyThe purpose of the study was to assess the occurrence of burnout syndrome among nurses employed in non-invasive treatment wards.Material and methods The research was conducted among nurses employed in non-invasive treatment wards in the Małopolskie voivodship. The research method in this work was a diagnostic survey. The auditorium questionnaire and a questionnaire standardized by Christina Maslach were used as the research technique. Respondents answered 26 questions from the personal questionnaire and 24 questions from the standardized questionnaire. The statistical analysis of the collected material was carried out in the Statistica 13.1 package from StatSoft, while the database and graphic design of the results were made in Microsoft Excel. Only non-parametric tests were used to analyze the variables. The statistical significance was assumed to be p<0.05.Results and conclusions The overall occupational burnout rate was 65.44. It depended on the age of the respondents and their seniority. Nurses with higher education had a lower rate of occupational burnout. The surveyed people who were better off had a lower burnout rate. More frequent stress experienced an increase in the burnout rate. Low wages and too small nursing staff have an impact on the occurrence of burnout syndrome of nurses. Stress in the workplace is one of the significant factors causing occupational burnout among nurses employed in non-invasive treatment wards.